Analysis of the Development of Physical Education Materials in Teaching Modules in Elementary Schools, State 2 North Loktabat, Banjarbaru City (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study is to analyse the development of Physical Education (PE) materials in the odd semester teaching module for Grade VI at State Elementary School 2 North Loktabat, Banjarbaru City. The analysis is grounded in Gallahue’s theory of movement concepts, which emphasises three fundamental aspects: effort, space, and relationship. This research employed a quantitative descriptive approach using a closed observation instrument to evaluate seven PE teaching modules. The results revealed that the space aspect demonstrated the highest level of fulfilment, with an average score of 91.79%, indicating strong representation of spatial awareness and locomotor movement planning. This was followed by the relationship aspect at 88.94%, reflecting satisfactory inclusion of peer interaction and cooperative learning elements. However, the effort aspect scored relatively lower at 78.89%, suggesting limited incorporation of movement dynamics such as force, time, and flow. A particularly significant gap was identified in the football module, which only achieved 20% fulfilment for the effort component. These findings highlight that although certain aspects of Gallahue’s framework are well represented, the effort dimension remains underdeveloped, especially in sport-specific modules. Therefore, the study underscores the importance of teacher training and curriculum enrichment to enhance the comprehensiveness and developmental alignment of PE modules. The research provides a foundational evaluation that can inform the design of more contextualised, effective, and child-centred PE teaching materials, particularly in the Indonesian elementary education context.